PENGARUH BIAYA LINGKUNGAN DAN UKURAN PERUSAHAAN TERHADAP KINERJA KEUANGAN - Rahandhika Ivan Adyaksana; Vidya Vitta Adhivinna; Lulu Amalia Nusron; Aure Nabilla Zahra Cheysa (LPPM STIE YKPN Yogyakarta, 2026)
This research examines the impact of environmental costs and company size on financial performance. The study was conducted on companies in the Consumer Cyclicals and Consumer Non-Cyclicals sectors listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. A quantitative method was applied using secondary data from annual and financial reports. All companies in the sector comprised the population, while the sample consisted of 92 companies selected through saturated sampling. Financial performance was measured using Return on Equity (ROE), environmental costs were assessed using the Environmental Cost Ratio (ECR), and company size was calculated based on the natural logarithm of total assets. Data analysis was conducted using multiple linear regression with the assistance of SPSS version 25. The findings indicate that environmental costs have a significant negative effect on financial performance, while company size has a significant positive effect. Collectively, these two variables were also proven to have a significant effect of 0.004 on financial performance.